2017
DOI: 10.3389/fnbeh.2017.00106
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Treatment with N-acetyl Cysteine Prevents the Development of Cognitive and Social Behavioral Deficits that Result from Perinatal Ketamine Treatment

Abstract: Alterations of the normal redox state can be found in all stages of schizophrenia, suggesting a key role for oxidative stress in the etiology and maintenance of the disease. Pharmacological blockade of N-methyl-D-aspartic acid (NMDA) receptors can disrupt natural antioxidant defense systems and induce schizophrenia-like behaviors in animals and healthy human subjects. Perinatal administration of the NMDA receptor (NMDAR) antagonist ketamine produces persistent behavioral deficits in adult mice which mimic a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 127 publications
(204 reference statements)
5
40
0
Order By: Relevance
“…6G) on social interaction. Consistent with our previous reports (Jeevakumar et al, 2015; Phensy et al, 2017b), WT-KET mice showed reduced investigation times across trials 1, 2, and 5. In contrast, Ppif -/- -KET mice demonstrated investigation times similar to saline-treated controls across all five exposures, suggesting normal social interaction and recognition memory.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…6G) on social interaction. Consistent with our previous reports (Jeevakumar et al, 2015; Phensy et al, 2017b), WT-KET mice showed reduced investigation times across trials 1, 2, and 5. In contrast, Ppif -/- -KET mice demonstrated investigation times similar to saline-treated controls across all five exposures, suggesting normal social interaction and recognition memory.…”
Section: Resultssupporting
confidence: 93%
“…These tasks included a rule-shifting task to measure cognitive flexibility, a novel object recognition task which measures (short-term) memory for objects, and a social interaction task which tests deficits in social interaction and novelty discrimination (Fig. 6) (Jeevakumar et al, 2015; Phensy et al, 2017b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations